Visualization of the Implementation of Cross-Cultural Counseling in the “Serawai” Tribe Based on Multimedia - Sari, Widya Kartika; Ariani, Winda Ade; Jannah, Nurul; Afrianti, Vira; Pattisinai, Amanda Ristriana; Wildani, Zakiatul (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
Visualization of the application of cross-cultural counseling is a counseling approach that involves counselors and clients from different cultural backgrounds, where cultural information is presented explicitly. In this process, the potential for cultural prejudice is very high, so counselors must have cultural sensitivity to ensure the effectiveness of counseling services. Each client carries a self-development cycle influenced by the local wisdom of their culture, including in the context of the Serawai tribe culture, especially in the relationship between young people known as